Pengaruh Return On Investment (ROI), Debt To Equity Ratio (DER) dan Ukuran Perusahaan terhadap Harga Saham pada Perusahaan Manufaktur Sektor Food dan Beverages yang terdaftar di Bursa Efek Indonesia (BEI) Tahun 2019-2022 - Astuti, Intan Novia; Ridha, Ainul (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIES Banda Aceh, 2024)
This study to analyze Return On Investment (ROI), Debt To Equity Ratio (DER) and Company Size on Stock Prices in Food and Beverages Sector Manufacturing Companies listed on the Indonesia Stock Exchange (IDX) in 2019-2022. The research method used is Multiple Linear Regression Analysis. The selected sample of this study was 18 companies and the observation year was 4 years. The sampling technique was Purposive Sampling. The variables of the application of Return On Investment (ROI), Debt To Equity Ratio (DER), Company Size and Stock Price were measured using a ratio scale, and the data used were secondary data. Analysis of research data using SPSS for Windows Software. The results of the study indicate that Return On Investment (ROI), Debt To Equity Ratio (DER) and Company Size together (simultaneously) affect Stock Prices in Food and Beverages Sector Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) in 2019-2022. Return On Investment (ROI), Debt To Equity Ratio (DER) and company size partially influence the Stock Price of Manufacturing Companies in the Food and Beverages Sector Listed on the Indonesia Stock Exchange (IDX) in 2019-2022.